Ta'lim al-Mufradat al-Lughah al-'Arabiyah bi istikhdami Bithaqah KUBAKU - Habibur Rahman (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2019)
Vocabulary is an important element of the Arabic language in developing students’ language proficiency. The development of vocabulary mastery is one of the objectives of any foreign language teaching plan, especially in teaching Arabic. This is because vocabulary serves as a vehicle for conveying meaning and, at the same time, as a tool for thinking. The researcher employed qualitative research using a descriptive approach at Nur al-Hasan Elementary School, Jarin, Pademawu, Pamekasan. The results of the study indicate that teaching Arabic vocabulary using KUBAKU cards is carried out through various teaching methods. The use of KUBAKU cards at Nur al-Hasan Elementary School in the third grade is in accordance with theories of teaching Arabic vocabulary for beginners in terms of their application. The methods used include the direct method, the reading-and-action method, the audio-lingual method, the question-and-answer method, game-based methods/strategies, the singing method, and the translation method. Through the use of KUBAKU cards at Nur al-Hasan Elementary School, teachers are able to enhance students’ motivation and elicit positive responses in vocabulary learning. For example, students are more diligent in learning and experience ease, enjoyment, and pleasure in the learning process. By using KUBAKU cards along with various teaching methods, all students are able to achieve the required and targeted competency standards in vocabulary learning set by the teacher. In other words, the use of these cards can improve learning outcomes and students’ comprehension in vocabulary instruction.